Risk Factors for Mandibular Fracture After Marginal Mandibular Resection. Issue 5 (July 2020) - Sukegawa, Shintaro; Saika, Masato; Tamamura, Ryo; Yamamoto, Norio; Nakano, Keisuke; Nagatsuka, Hitoshi; Furuki, Yoshihiko
Abstract : Purpose: This study aimed to examine the relationship between post-operative mandibular fractures and its predictable risk factors in patients with marginal mandibular resection. Additionally, the timing of post-operative mandibular fractures was assessed. Patients and methods: Records of 37 patients with mandibular gingival carcinoma who underwent marginal mandibular resection at the Department of Oral and Maxillofacial Surgery, Kagawa Prefectural Central Hospital, from April 2011 to March 2019 were retrospectively analyzed. The following variables were investigated: age, sex, location of carcinoma, tumor size, mandibular height on the surgical and healthy sides, surgical approach, number of residual teeth, post-operative radiotherapy, chemotherapy, and the presence or absence of diabetes and osteoporosis. Various risk factors for post-operative mandibular fractures were statistically investigated. Results: Post-operative mandibular fracture was observed in 5 (13.5%) of the 37 mandibular marginal resection cases. The average residual mandibular height in patients with post-operative mandibular fracture was 8.5 mm. A significant difference in residual mandibular height ( P  = 0.013) was observed between patients with post-operative mandibular fracture and those with no fracture. The average time to post-operative fracture of the mandible was 305.4 days, and it was found to be correlated to the remaining height of the mandibular body. Conclusions: A decrease in mandibular height below 9 mm results in post-operative mandibular fracture. Furthermore, a correlation between the height of the mandibular bone and the period until the post-operative mandibular fracture was noted in this study. These findings contribute to the prediction and management of mandibular fractures after mandibular margin resection. Abstract : Supplemental Digital Content is available in the text